Using a bimanual lever-driven wheelchair for arm movement practice early after stroke: A pilot, randomized, controlled, single-blind trial. (November 2021) - Smith, Brendan W; Lobo-Prat, Joan; Zondervan, Daniel K; Lew, Christopher; Chan, Vicky; Chou, Cathy; Toledo, Spencer; Reinkensmeyer, David J; Shaw, Susan; Cramer, Steven C
Objective: Many patients with subacute stroke rely on the nonparetic arm and leg to propel manual wheelchairs. We designed a bimanual, lever-driven wheelchair (LARA) to promote overground mobility and hemiparetic arm exercise. This study measured the feasibility of using LARA to increase arm movement, achieve mobility, and improve arm motor recovery (clinicaltrials.gov/ct2/show/NCT02830893). Design: Randomized, assessor-blind, controlled trial. Setting: Two inpatient rehabilitation facilities. Subjects: Nineteen patients with subacute stroke (1 week to 2 months post-stroke) received 30 minutes extra arm movement practice daily, while admitted to inpatient rehabilitation ( n = 10) or before enrollment in outpatient therapy ( n = 9). Interventions: Patients were randomized to train with the LARA wheelchair ( n = 11) or conventional exercises with a rehabilitation therapist ( n = 8). Main measures: Number of arm movements per training session; overground speed; Upper Extremity Fugl-Meyer score at three-month follow-up. Results: Participants who trained with LARA completed 254 (median) arm movements with the paretic arm each session. For three participants, LARA enabled wheelchair mobility at practical indoor speeds (0.15–0.30 m/s). Fugl-Meyer score increased 19 ± 13 points for patients who trained with LARA compared to 14 ± 7 points with conventional exercises ( P = 0.32). Secondary measures including shoulder pain and increased tone did not differ between groups. Mixed model analysis found significant interaction between LARA training and treatment duration ( P = 0.037), informing power analysis for future investigation. Conclusions: Practising arm movement with a lever-driven wheelchair is a feasible method for increasing arm movement early after stroke. It enabled wheelchair mobility for a subset of patients and shows potential for improving arm motor recovery.